PHENOLIC, FLAVONOID CONTENT AND ANTIOXIDANT ACTIVITY WITH SUN PROTECTION FACTOR VALUE OF RED BETEL LEAF ETHANOL EXTRACT (Piper ornatum N. E. Br) - Yuniarti, Rafita; Rani, Zulmai; Ridwanto, Ridwanto; Lubis, Minda Sari (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2025)
Red betel leaf is a plant that is rich in benefits, one of which is as an antioxidant. The benefits as an antioxidant in plants are due to the content of phenolic and flavonoid compounds. Phenolic compounds also function as protection against UV-B rays, this ability can be seen from the SPF value. The purpose of this study was to determine the amount of phenolic and flavonoid compounds and the antioxidant and sunscreen activity of ethanol extract from red betel leaves. Phenolic content was determined using 10% Follin Ciocalteu reagent and 20% Na2CO3. In contrast, flavonoid content used AlCl3 and CH3COONa solutions, and the determination of antioxidant activity was carried out using DPPH. In contrast, the ability a protect against sunlight (sunscreen) was carried out by determining the sun protection factor (SPF) value. After measurements were carried out using a UV-visible spectrophotometer, the results obtained were a phenolic content of 257.56 mg GAE/g and flavonoids of 46.8008 mg QE/g. They had a very strong antioxidant activity with an IC50 value of 38.9338 ppm and had sunscreen activity with an SPF value of 5, 17, 28, 36, and 38 at concentrations of 100, 300, 500, 700, and 1000 ppm respectively.